Primary dysmenorrhea and self-care strategies among Chinese college girls: a cross-sectional study. Issue 9 (18th September 2019) - Chen, Ling; Tang, Lu; Guo, Shengyu; Kaminga, Atipatsa Chiwanda; Xu, Huilan
Abstract : Objectives: To explore the prevalence of primary dysmenorrhea (PD), the characteristics of PD and self-care strategies for managing PD among Chinese college girls. Design: Cross-sectional study. Setting: Changsha, China. Participants: A total of 2555 college girls were recruited using multistage cluster random sampling. Outcome measures: A self-report questionnaire was used to measure sociodemographic information, characteristics of PD and self-care strategies for managing PD. Additionally, a Visual Analogue Scale was used to measure pain severity. Results: Of the 2555 girls, 1306 had experienced PD, representing a 51.1% prevalence. In addition, the prevalence rates of mild, moderate and severe pain in PD were 18.1%, 27.7% and 5.4%, respectively. The most common symptoms associated with PD were cramps (96.9%), weakness (70.0%), backache (65.1%), facial blemishes (55.3%) and irritability (55.3%). Commonly used self-care strategies for managing PD comprised reducing physical activity (94.6%), keeping warm (84.6%), communicating dysmenorrhea with friends or classmates (79.0%), drinking warm beverages (75.7%) and avoiding cold drinks and foods (74.2%). In addition, only 34.8% self-medicated with Western medicine (15.6%), traditional Chinese medicine (8.6%), or both (10.6%). Medical advice was sought by 27.4% of subjects from a Western medical doctor (10.3%), a doctor of traditional Chinese medicine (13.6%), or both (3.5%). Girls who had greater pain severity were more likely to be self-medicated (OR=7.01; 95% CI 4.50 to 10.91), use complementary therapies (OR=2.64; 95% CI 1.70 to 4.10) and seek medical advice (OR=5.93; 95% CI 3.80 to 9.24). Conclusions: PD is highly prevalent among Chinese college girls, with a high burden of symptoms. In addition, these girls are most likely to change their lifestyle, communicate dysmenorrhea with friends or mothers, use heat therapy and engage in self-talk, but less likely to self-medicate or seek medical advice for managing PD.